Às margens dos destinos: as mortes e o sentimento de quem fica entre os Karajá de Ibutuna - Scartezini, Sofia Santos (Universidade Federal de São Carlos, 2019)
This research deals with the complexities involving the cases of death by bàtòtàka, a spell of "tying the throat" among the Karajá. The objective is, based on the ethnographic analysis of suicide cases in several indigenous contexts, to approach the specificities surrounding the understanding of these phenomena, in order to produce a discussion about the different meanings, based on the particularities of each context in the light of the cases of the inỹ autocides, Karajá’s self-denomination. Thus, this dissertation is constructed using as a literary and discursive resource the story "The Third Margin of the River" by Guimarães Rosa, and the ethnographic accounts of those who stand before the margin and have to deal with the economy of the various cosmos and inỹ beings, In this context, classical themes to Brazilian indigenous ethnology are addressed, such as: the notion of the person, corporeality, as well as the funerals, destinies reserved for the dead and ritual interruptions in the face of these fatalities, which, in Karajá’s context, give to the dead a destiny seen as awkward. In this way, I developed my work in the Ibutuna village, which is located along the Araguaia River, in the northwest portion of Bananal Island, on the border between Mato Grosso and Tocantins states.
La troisième rive: les morts et les sentiments de ceux qui restent parmi les Karajá de Ibutuna
Keywords: Inỹ-Karajá; Suicídio; Ritual; Exéquias; Suicide; Ritual; Obsequies; CIENCIAS HUMANAS::ANTROPOLOGIA::ETNOLOGIA INDIGENA